Associations of VEGF-C genetic polymorphisms with urothelial cell carcinoma susceptibility differ between smokers and non-smokers in Taiwan. - Min-Che Tung; Ming-Ju Hsieh; Shian-Shiang Wang; Shun-Fa Yang; Shiou-Sheng Chen; Shih-Wei Wang; Liang-Ming Lee; Wei-Jiunn Lee; Ming-Hsien Chien (PLoS ONE, 2014)
BACKGROUND: Vascular endothelial growth factor (VEGF)-C is associated with lymphangiogenesis, pelvic regional lymph node metastasis, and an antiapoptotic phenotype in urothelial cell carcinoma (UCC). Knowledge of potential roles of VEGF-C genetic polymorphisms in susceptibility to UCC is lacking. This study was designed to examine associations between VEGF-C gene variants and UCC susceptibility and evaluate whether they are modified by smoking. METHODOLOGY/PRINCIPAL FINDINGS: Five single-nucleotide polymorphisms (SNPs) of VEGF-C were analyzed by a TaqMan-based real-time polymerase chain reaction (PCR) in 233 patients with UCC and 520 cancer-free controls. A multivariate logistic regression was applied to model associations between genetic polymorphisms and UCC susceptibility, and to determine if the effect was modified by smoking. We found that after adjusting for other covariates, individuals within the entire population and the 476 non-smokers carrying at least one A allele at VEGF-C rs1485766 respectively had 1.742- and 1.834-fold risks of developing UCC than did wild-type (CC) carriers. Among the 277 smokers, we found that VEGF-C rs7664413 T (CT+TT) and rs2046463 G (AG+GG) allelic carriers were more prevalent in UCC patients than in non-cancer participants. Moreover, UCC patients with the smoking habit who had at least one T allele of VEGF-C rs7664413 were at higher risk of developing larger tumor sizes (p = 0.021), compared to those patients with CC homozygotes. CONCLUSIONS: Our results suggest that the involvement of VEGF-C genotypes in UCC risk differs among smokers compared to non-smokers among Taiwanese. The genetic polymorphism of VEGF-C rs7664413 might be a predictive factor for the tumor size of UCC patients who have a smoking habit.